Pengaruh Pendekatan Outdoor Learning terhadap Pemahaman Konsep Siswa pada Materi Bagian Tubuh Tumbuhan - Iis Nuraida Mulyaningsih; Atep Sujana; Rana Gustian Nugraha (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This research is to see the effect of a treatment in learning, namely Outdoor Learning on students' concept understanding on the material of plant body parts and also to see how the implementation of outdoor learning on students' concept understanding. The method used in the research is pre-experiment design One Group Pretest Posttest Design to 30 students in one of the State Elementary Schools in Sumedang, where the pretest is done by students before being given treatment then students do the posttest after being given treatment. The data analysis technique used in this research is quantitative descriptive analysis, namely data normality test, and Differential Test. The results of this data processing get a significant difference when the data generated by the Normality Test is normally distributed which is then carried out a different test, namely the paired sample t-test test because the data generated is normal then obtains a significant value of 0.000 <0.05, so the hypothesis is accepted. The results of this study indicate that there are differences in students' concept understanding before and after being given the Outdoor Learning approach to the material of plant body parts.